(untitled) (Social Science Review, 2026)
This study presents a comparative analysis of Bengali political and celebrity interviews in the context of institutional Conversation Analysis (CA). This study uses a descriptive qualitative method. The data consisted of institutional talk (interviews) conducted by a political leader and a celebrity, with two journalists (interviewers) from two local and international Bangla news channels. This study aimed to investigate significant differences between political and celebrity interviews in Bengali. To answer the question, two selected Bangla political and celebrity conversations are analysed according to the framework of Clayman and Heritage (2002). The Jefferson Transcription system (2004) is used to produce the analysis results. From this research, it is evident that in a news interview, the views of both interviewers and interviewees can be presented to the public through questions and answers, thereby creating the context of their accountability to the public. Similarly, this study shows how the interviewer maintains a neutral position in news interviews through adversarial questioning and how politicians exhibit evasiveness or resistance in answering those questions. In contrast, this analysis reveals that a Bengali celebrity interview typically employs a non-adversarial, unchallenging question-and- answer format, in which the interviewer elicits personal and professional information from celebrities in a polite, congenial manner for the public. Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 265-284